Idő és pénz a gyereknevelésben Magyarországon, 1993-2010 - Tamás Hajdu; Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
– This study examines social differences in time use and expenditures and their evolution over time among families with young children. The analysis is based on the KSH Time Use and Household Budget Surveys. Our results show that families with higher educational attainment spend more on items and activities of enrichment than families with lower educational attainment. In addition, higher educated mothers and fathers also spend more time on childcare and activities that directly or indirectly develop their children's skills than parents with lower education. The differences are enormous. On average, two-child families where both parents have tertiary education spend 350 hours more on childcare activities and 400 thousand HUF more on items and activities of enrichment than families where the parents have secondary education. In addition, we also see significant changes over time. Social differences in time spent with children and enrichment expenditure have increased during the 1990s and 2000s.
Keywords: J13; J22; 330; time use; childcare; enrichment expenditures; social inequality